Relationship between transfusion volume and outcomes in children undergoing noncardiac surgery. Issue 10 (12th July 2016) - Goobie, Susan M.; DiNardo, James A.; Faraoni, David
Abstract : BACKGROUND: The objective of this study was to assess the relationship between the volume of red blood cells (RBCs) transfused and outcomes in children undergoing noncardiac surgery. STUDY DESIGN AND METHODS: Children undergoing noncardiac surgery recorded in the 2012 and 2013 American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) pediatric databases were included. Outcomes included 30‐day mortality and the incidence of major postoperative complications. Children who received RBC transfusions were further classified into four subgroups based on the volume transfused. We used multivariable logistic regression analysis and propensity‐matched analysis to match each child who received a transfusion with a nontransfused control and to compare the incidences of 30‐day mortality and adverse postoperative outcomes. RESULTS: After propensity‐matched analysis, there were 4496 children in the group that received transfusion volumes from 1 to 19 mL/kg, 1557 in the group that received volumes from 20 to 39 mL/kg, 506 in the group that received from 40 to 59 mL/kg, and 412 in the group that received ≥60 mL/kg. Children who received RBC transfusion volumes from 40 to 59 mL/kg and ≥60 mL/kg had an increased risk for 30‐day mortality of 7.3% versus 1.4% (p < 0.001) and 11.2% versus 2.9% (p = 0.005), respectively, compared with their matched controls. No statistical difference was reported for children who were exposed to transfusion volumes from 20 to 39 mL/kg (3.3% vs 1.3%; p = 0.021), or from 1 to 19 mL/kg (1.4% vs. 1.2%; p = 0.691). Although no effect was observed on the incidence of postoperative renal failure or wound complications, RBC transfusions were associated with an increased incidence of postoperative infection when the volume transfused exceeded 20 mL/kg. CONCLUSIONS: RBC transfusion is associated with an increased incidence of 30‐day mortality and postoperative infections in children undergoing noncardiac surgery, and there is a correlation between the volume of red blood cells transfused and the incidences of adverse outcomes. Potential associations related to the reason to transfuse, the cause of the bleeding, or the actual blood products themselves need to be studied in further prospective trials.